Spinopelvic Parameters in Anterior Lumbar Interbody Fusion, the First Follow-Up Study of Three Years in Mexican Population - Quillo-Olvera, Diego; Quillo-Olvera, Javier; Quillo-Resendiz, Javier; Vega-Sosa, Alfonso (International Journal of Innovative Research in Medical Science, 2019)
Objective: The objective of this work is to identify the modifications of the spinopelvic balance posterior to the ALIF and therefore its clinical repercussion. Methods: A retrospective study of 20 patients were included, patients treated with ALIF was performed by 2 neurosurgeons and 1 vascular surgeon in 1 medical center in 2015, clinical data and radiographic measurements pre and postoperative at 3 years follow-up were studied. Results: The number of patients was 20;16 females (80%) and 4 males (20%), with a follow-up 36 months, the mean age of the studied group was 50.1 ± 8.5years (range 35-67 years), body mass index (BMI) was 29± 3.5, two of the 20 patients (10%) had undergone prior spine surgery, a total of 26 ALIF levels were treated in 20 patients, fourteen patients (70%) underwent 1 level L5-S1 and six patients (6%) underwent 2 level L4-L5,L5-S1. All ALIF cages were supplemented with anterior integrated fixation, Eigth(40%) of 20 patients were treated with posterior spinal fixation in addition to their ALIF procedure, Twelve (60%) of 20 patients were standalone ALIF. The mean hospital stay after ALIF procedure were 4.05± 1.87 days (range 2-9 days). PI,SS,PT and LL were measures pre and the postoperative was the last reported during the 3 years follow up, PI and SS has statistically significant (p= 0.008 and 0.012)correspondingly. visual analog scale (VAS) was the measure preoperative and the postoperative was the last reported getting statistically significant (p= 0.001) and the complications obtained in 4 cases were persistent pain, bleeding, intestinal pseudoclusion and retrograde ejaculation. Conclusions: The interaction between the anatomy of the pelvis and the paravertebral muscles have a direct influence on the stress of the intervertebral discs, improving the posture of the spine and minimizing energy expenditure. In this work performed the changes in the espinopelvic parameters that are described in the literature were obtained; we know that the ALIF improves the pelvic incidence and therefore the lumbar lordosis postoperative. Here we could verify that the modification of spinopelvic balances is related to the clinical improvement of the patient in the follow-up after his surgery, however is necessary to demonstrate quantitatively the modification of these parameters in our population to justify that the surgery is a satisfactory result for the patient.